Axial-Flow Pump with Enhanced Cavitation Erosion Resistance - Aleksandr Zharkovskii; Dmitry Svoboda; Igor Borshchev; Arsentiy Klyuyev; Evgeniy Ivanov; Sergey Shutsky (Energies, 2023)
Axial-flow pumps, in addition to providing high anti-cavitation properties, must have high anti-erosion properties to ensure the required lifetime of the pump. Erosion damage of surfaces occurs when the net positive suction head (NPSH) significantly exceeds its critical value. The object of the study in this article is the axial-flow pump with a specific speed of 600 in two alternatives: № 1 and № 2. By analysis of the flow in the impeller blade systems, the ratio value between the NPSH, which ensures the absence of erosion, and the NPSH3, at which pump operational failure occurs, was determined. Impeller variant № 1 did not provide the required ratio. Impeller variant № 2 had higher cavitation qualities, and the required ratio was achieved for it. Energy, cavitation, and erosion characteristics of the axial-flow pump with impeller № 2 in rotational frequency n = 2000 rpm were investigated. Easily breakable paint coatings were used for the accelerated study of cavitation erosion. The experiment was carried out at three different flow rates and confirmed the assumptions made—the pump with impeller № 2 was not affected by cavitation erosion at the optimum flow rate. Patterns of erosion zones were accompanied by calculations of vapor zones in the impeller. At flow rates less than the optimum, cavitation disruptions occurred and appeared behind the vapor region. As a result, the condition of ensuring erosion-free flow in the impeller of an axial pump with a specific speed of 600 was obtained, ensuring the ratio NPSH/NPSH3 > 2.5. Recommendations on designing of erosion-free flow part of the axial pump impeller were also obtained.